2004
DOI: 10.21273/hortsci.39.7.1553
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Resistance of Red Raspberry (Rubus idaeus L.) Genotypes to Phytophthora fragariae var. rubi in Hydroponic Culture

Abstract: A hydroponic method was developed and tested for screening red raspberry genotypes for resistance to Phytophthora fragariae var. rubi, the most common causal agent of Phytophthora root rot in raspberry. Plants of `Titan' and `Encore' exhibited typical disease symptoms, with the latter developing significantly smaller stem lesions and fewer petiole lesions. The resistant cultivar, `Latham', regenerated healthy root tissue from the crown and older-ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 17 publications
(29 reference statements)
0
14
0
Order By: Relevance
“…'Cascade Bounty' had resistance similar to that of 'Newburgh' in the greenhouse, which agrees with earlier field observations (Moore and Finn, 2007), although confirmation is needed from a replicated field study. Pattison et al (2004) observed that a cultivar's ability to generate new primocanes from root tissue rather than existing crown tissue may allow it to recover from moderate or intermittent root rot infection in the field. However, such a recovery mechanism may not be apparent in a short-term greenhouse test with high disease pressure, leading to a susceptibility rating higher than observed in the field (Pattison et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…'Cascade Bounty' had resistance similar to that of 'Newburgh' in the greenhouse, which agrees with earlier field observations (Moore and Finn, 2007), although confirmation is needed from a replicated field study. Pattison et al (2004) observed that a cultivar's ability to generate new primocanes from root tissue rather than existing crown tissue may allow it to recover from moderate or intermittent root rot infection in the field. However, such a recovery mechanism may not be apparent in a short-term greenhouse test with high disease pressure, leading to a susceptibility rating higher than observed in the field (Pattison et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…A few cultivars are resistant to root rot such as 'Newburgh' and 'Latham', but most commercial cultivars are susceptible to root rot and eventually show disease symptoms (Pattison et al, 2004). These include 'Meeker', which accounts for more than 70% of raspberry plantings in the Pacific Northwest (Washington Red Raspberry Commission, 2004), and 'Willamette' (Barritt et al, 1981).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Above-ground symptoms of root rot usually appear within 10 weeks and susceptible genotypes are dead within 15 weeks while resistant seedlings grow vigorously (Daubeny 1996 ) . Pattison et al ( 2004 ) developed an effective hydroponic procedure to conduct screening for resistance. Young seedlings can be pre-fi eld screened for resistance to other diseases and pests according to the relative importance of the problem and the practicality of the screening.…”
Section: Breeding Methodologymentioning
confidence: 99%
“…The sources of resistance used in this breeding are from 'Cherokee' and 'Latham' and, by selecting in fi elds heavily infested with P. rubi , they have identifi ed individuals with high fi eld resistance. The New York program is screening for P. rubi in the fi eld and in hydroponic systems in the greenhouse (Pattison et al 2004 ) . 'Prelude,' 'Heritage,' and 'Taylor' show good fi eld resistance to P. rubi .…”
Section: Resistance To Diseasesmentioning
confidence: 99%